Implication of microglia activation and CSF1/CSF1R pathway in lumbar disc degeneration-related back pain. Issue 1 (November 2018) - Yang, Ge; Chen, Lunhao; Gao, Zhihua; Wang, Yue
Back pain is common and costly. Although lumbar disc degeneration has long been regarded as a major contributor to back pain, how disc degeneration leads to back pain remains unclear. Recent studies observed microglia activation in the spinal cord after disc degeneration, suggesting activated microglia may be involved in discogenic back pain. To determine whether microglia activation participates in disc degeneration-induced back pain, we used a modified disc puncture-induced degeneration-related back pain mouse model to examine the changes in spinal microglia and investigate the potential link between microglia activation and discogenic back pain. In this study, 46 CX3CR1 GFP/+ male mice were used in experimental and sham groups. A modified posterolateral retroperitoneal approach was used to expose the L3/L4 disc to induce the needle puncture in the experimental group. Behavioral tests, including grip force and physical function, were used to measure back pain at pre- and postsurgery. The L3 dorsal root ganglions and lumbar spinal cord were obtained at postoperative weeks 1 to 4 followed by immunofluorescence with different antibodies. Micrographs were obtained by confocal microscopy, and morphometric measurements of microglia were analyzed using Imaris. The punctured disc underwent progressive degeneration and mice with disc degeneration showed impaired grip force and physical function. Compared to the control mice, the number of microglia in the lumbar spinal cord was significantly increased in the disc-punctured animals. Moreover, accumulated microglia exhibited larger soma size and lesser ramification in the disc-injured mice. Immunofluorescence demonstrated colony-stimulating factor 1, a cytokine that promotes microglia repopulation, was significantly increased in L3 dorsal root ganglions, whereas its receptor colony-stimulating factor 1 receptor was upregulated on microglia in the disc-injured mice. In summary, lumbar disc puncture caused progressive disc degeneration which induced microglia activation and back pain in mice. Increased colony-stimulating factor 1/colony-stimulating factor 1 receptor signaling is involved in the disc degeneration-induced microglia activation and back pain.